2021
DOI: 10.1111/2047-3095.12342
|View full text |Cite
|
Sign up to set email alerts
|

Qualitative examination of the attitudes of healthcare workers in Turkey regarding COVID‐19 vaccines

Abstract: Purpose The attitudes of healthcare workers toward COVID‐19 vaccines ensure that health services are able to run without interruption and potentially have a role in the messaging about vaccination that they convey to the public. Hence, healthcare workers’ attitudes ultimately have a significant role in controlling the pandemic. This study aimed to qualitatively investigate the attitudes of healthcare workers in Turkey in relation to COVID‐19 vaccines. Methods The study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 49 publications
(79 reference statements)
0
15
0
Order By: Relevance
“…Some may have also incorrectly categorized the vaccine as "experimental" and may feel that their receipt of the vaccine post-approval is participation in an ongoing experiment [231,232] even though monitoring of adverse events continues after FDA approval (known as Phase IV) is a standard procedure for all pharmaceuticals. A small number of HCWs also subscribed to fringe or conspiracy theories about COVID-19, including that COVID-19 is a hoax [110].…”
Section: Vaccination Unnecessarymentioning
confidence: 99%
See 1 more Smart Citation
“…Some may have also incorrectly categorized the vaccine as "experimental" and may feel that their receipt of the vaccine post-approval is participation in an ongoing experiment [231,232] even though monitoring of adverse events continues after FDA approval (known as Phase IV) is a standard procedure for all pharmaceuticals. A small number of HCWs also subscribed to fringe or conspiracy theories about COVID-19, including that COVID-19 is a hoax [110].…”
Section: Vaccination Unnecessarymentioning
confidence: 99%
“…Finally, although HCWs are often seen as distinct from the general public, they are susceptible to the same emotions, biases, concerns, and assumptions that the general population has. A survey of HCWs in Turkey in January 2021 noted some respondents expressing feelings of anxiety, hopelessness, and helplessness regarding the pandemic and issues around vaccination [232]. Stresses from the pandemic, both professionally and personally, may lead to burnout and possibly higher rates of complacency regarding health-protective measures.…”
Section: Towards the Futurementioning
confidence: 99%
“…A study about parental acceptability of COVID-19 vaccination for children shows that longer protection duration of vaccine-associated with higher parental acceptability of COVID-19 vaccination [35]. The uncertainty of the duration of protection has caused the hesitation of healthcare workers to be vaccinated [36]. How long the duration of protection is acceptable needs to be further explored.…”
Section: Perceived Vaccine Effectiveness and Duration Of Protectionmentioning
confidence: 99%
“…Another study reported that safety of vaccines influenced willingness to be vaccinated [29]. Studies have also shown that vaccine hesitancy may be influenced by several other factors, including the rapid development of COVID-19 vaccines globally, thinking that vaccines have not been used and tested for a sufficient period of time, thinking that a new vaccine is not needed, and limited public knowledge and misinformation [3,30].…”
Section: Discussionmentioning
confidence: 99%
“…This study found that the country of origin of vaccines was a factor involved in vaccine-related decisions. Acı et al [30] found that vaccine myths and prejudices about the country in which the vaccine was developed influence vaccination decisions. In line with our results, the same study reported that some participants were biased toward the country of origin of the vaccine and would prefer waiting for a domestic vaccine.…”
Section: Discussionmentioning
confidence: 99%